SISTEM PENDUKUNG KEPUTUSAN PENDUGAAN UMUR SIMPAN & TANGGAL KADALUARSA PRODUK PANGAN DENGAN METODE ARRHENIUS BERBASIS WEB - Irfianti, Asti Dwi; STP, MP, Rosida (UPN VETERAN JAWA TIMUR, 2010)
The concept of Decision Support Systems is one branch of artificial intelligence which is widely used. There are many methods that can be used by decision makers to find the optimum solution or alternative to a problem. One such method is the method of Arrhenius. This method will help decision makers where many alternative decisions with multiple criteria. This research will apply prediction shelf life and expiration dates with three different temperatures. At this time in the counting process prediction shelf life expiration date carried out by conventional means which are found to be inefficient, with the Arrhenius method pangaplikasian writer trying to create an auxiliary system for processing plant food products to determine shelf life and expiration date. The input data research, the raw data is processed into a desired output based on the parameters taken. The methodology is the identification of system requirements with system modeling, analysis, information needs of data storage with a conceptual data model and physical data models as the material content of the material system. Test the feasibility of web-based Decision System is done by performing a series of test scenarios include: test parameters, product testing, trials of sub products, organoleptic test data (research data).Keywords: shelf life, organoleptic data, Artificial Intelligence, Decision Support System